Building the foundation to generate a fundamental care standardised data set. Issue 11 (6th April 2018) - Jeffs, Lianne; Muntlin Athlin, Asa; Needleman, Jack; Jackson, Debra; Kitson, Alison
Abstract : Aim and objectives: This paper provides an overview of the current state of performance measurement, key trends and a methodological approach to leverage in efforts to generate a standardised data set for fundamental care. Background: Considerable transformation is occurring in health care globally with organisations focusing on achieving the quadruple aim of improving the experience of care, the health of populations, and the experience of providing care while reducing per capita costs of health care. In response, healthcare organisations are employing performance measurement and quality improvement methods to achieve the quadruple aim. Despite the plethora of measures available to health managers, there is no standardised data set and virtually no indicators reflecting how patients actually experience the delivery of fundamental care, such as nutrition, hydration, mobility, respect, education and psychosocial support. Conclusions: Given the linkages of fundamental care to safety and quality metrics, efforts to build the evidence base and knowledge that captures the impact of enacting fundamental care across the healthcare continuum and lifespan should include generating a routinely collected data set of relevant measures. Relevance to clinical practice: This paper provides an overview of the current state of performance measurement, key trends and a methodological approach to leverage in efforts to generate a standardised data set for fundamental care. Standardised data sets enable comparability of data across clinical populations, healthcare sectors, geographic locations and time and provide data about care to support clinical, administrative and health policy decision‐making.